2023
DOI: 10.1038/s41598-023-31882-4
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic synapses onto SST and PV interneurons in the CA1 hippocampal region show cell-specific and integrin-dependent plasticity

Abstract: It is known that GABAergic transmission onto pyramidal neurons shows different forms of plasticity. However, GABAergic cells innervate also other inhibitory interneurons and plasticity phenomena at these projections remain largely unknown. Several mechanisms underlying plastic changes, both at inhibitory and excitatory synapses, show dependence on integrins, key proteins mediating interaction between intra- and extracellular environment. We thus used hippocampal slices to address the impact of integrins on lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
(98 reference statements)
1
4
0
Order By: Relevance
“…Thus, the overall synchronization of principal cells activity may be expected to increase (Pouille and Scanziani, 2001). Simultaneously, in the present report, we observed the upregulation of tonic inhibition in somatostatin-containing interneurons that target principal cells' dendrites in stratum lacunosum-moleculare, and this effect is accompanied by increased iLTP of mIPSCs (Brzdak et al, 2023). Considering that SST+ interneurons regulate local dendritic conductances and also excitatory synaptic plasticity, an increase in their tonic inhibition may result in less feedback inhibition onto principal cells (Chiu et al, 2013;Schulz et al, 2018).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Thus, the overall synchronization of principal cells activity may be expected to increase (Pouille and Scanziani, 2001). Simultaneously, in the present report, we observed the upregulation of tonic inhibition in somatostatin-containing interneurons that target principal cells' dendrites in stratum lacunosum-moleculare, and this effect is accompanied by increased iLTP of mIPSCs (Brzdak et al, 2023). Considering that SST+ interneurons regulate local dendritic conductances and also excitatory synaptic plasticity, an increase in their tonic inhibition may result in less feedback inhibition onto principal cells (Chiu et al, 2013;Schulz et al, 2018).…”
Section: Discussionsupporting
confidence: 82%
“…This mechanism has been, however, implicated in the pyramidal neurons, and it remains to be elucidated whether or not it takes place also in interneurons investigated in the present study. In our recent study (Brzdak et al, 2023), we report that a brief treatment with NMDA evoked iLTP in SST+ and iLTD in PV+ interneurons. Thus, the effects on tonic conductance (present study) would thus sum up with analogous changes in phasic signaling in these neurons (Brzdak et al, 2023).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Recently, our group has revealed that integrins modulate GABAergic synaptic transmission and plasticity. Specifically, interference with integrin-dependent adhesion blocks the induction of NMDA-iLTP in CA1 pyramidal cells or interneurons [20], [57]. However, we did not observe changes in levels of extended, presumably active, forms of integrin β1 or β3 (Fig.…”
Section: Potential Role Of Integrinsmentioning
confidence: 59%